Social Media and Information Exchange among Nigerian Youths Considering Japa Syndrome - Oluwatoyosi, Ajayi David (Journal of Information and Knowledge, 2025)
This study investigates the phenomenon of “Japa Syndrome” among Nigerian youth, focusing on the influence of social media on their aspirations for emigration. Utilising a mixed-method approach, including surveys and interviews, the research examines how social media shapes perceptions, facilitates information exchange, and forms support networks related to emigration. Theoretical frameworks such as the Push-Pull Theory of Migration, Social Capital Theory, and Uses and Gratifications Theory guide the analysis. Findings indicate that social media serves as a significant source of information and support for Nigerian youth considering emigration, while also perpetuating aspirational narratives and unrealistic expectations. Recommendations include promoting digital literacy, creating economic opportunities, fostering positive narratives, strengthening social support networks, and facilitating dialogue among stakeholders. This study contributes to understanding Japa Syndrome and provides insights for policy and intervention strategies to empower Nigerian youth and promote sustainable development within the country.